User Perceptions and Satisfaction Levels with Pathao Services in Nepal - Bhat, Chudamani Singh; Mahato, Bikesh Kumar; Nepali, Bijeta (NPRC Journal of Multidisciplinary Research, 2024)
Background: Pathao, a leading ride-sharing and delivery service in Nepal, has gained significant popularity, especially among younger demographics. Understanding customer perceptions, usage patterns, and satisfaction levels is crucial for Pathao to enhance its offerings and maintain its competitive edge in the growing market.Objective: This study aims to evaluate user awareness, service adoption, satisfaction levels, and areas of improvement for Pathao services in Nepal.Methods: A structured survey was conducted among 59 respondents to gather data on demographic characteristics, service usage preferences, and customer satisfaction. Responses were analyzed using frequency and percentage distributions to identify key trends and insights.Findings: The results indicate a high level of awareness (96.6%) and adoption (89.8%) of Pathao services, with ride-sharing being the most preferred service (45.8%). The majority of users belong to the 18-24 age group (76.3%) and are male (66.1%). Customer satisfaction is notable in areas such as service availability (71.2%) and responsiveness (52.5%), but some users expressed neutrality or dissatisfaction regarding peak-time charges (49%) and vehicle cleanliness (47.5%). A significant portion (54.2%) is likely to recommend Pathao, highlighting strong word-of-mouth potential.Conclusion: Pathao has established itself as a trusted service provider among its core demographics. However, addressing concerns related to dynamic pricing, vehicle cleanliness, and tailored services for female users can enhance satisfaction and loyalty.Novelty: This study offers a comprehensive analysis of customer experiences with Pathao in Nepal, providing actionable insights to bridge service gaps and improve market positioning in a competitive landscape.